Strategies for improving the performance of embroidery craft businesses in the digital era - Nusron, Anis (Institute of Accounting Research and Novation (IARN), 2024)
This study aims to examine the effect of information technology and entrepreneurial characteristics on business performance and determine the mediating effect of entrepreneurial behavior in selling online. novelty in this study is the variable of entrepreneurial behavior in selling online which is based on the merger of 2 theories, namely TAM theory and Sales Process / Behaviour theory. Sampling using non-probability samples with purposive sampling, the research was conducted on embroidery business actors in Pasuruan Regency, Indonesia, by taking 180 samples, WarpPLS was used as an analytical tool to process data. The results showed that information technology and entrepreneurial behavior in selling online have a significant positive effect on business performance while entrepreneurial characteristics have no effect on business performance. Information technology and entrepreneurial characteristics have a significant effect on entrepreneurial behavior in selling online. and entrepreneurial behavior in selling online is able to mediate information technology and entrepreneurial characteristics on business performance. Digital activities as a selling medium for embroidery business actors in Pasuruan Regency are new to business actors, this research expands the view of activities in selling online and increases the literature on entrepreneurship, besides that it can be useful for MSMEs to improve business performance, and encourage related parties to support MSMEs in Indonesia to be able to improve their skills in selling online, because the results of the study show that entrepreneurial behavior in selling is able to improve business performance.